2003
DOI: 10.1515/revneuro.2003.14.4.303
|View full text |Cite
|
Sign up to set email alerts
|

The Human Amygdala: An Evolved System for Relevance Detection

Abstract: SYNOPSISEvidence from pioneering animal research has suggested that the amygdala is involved in the processing of aversive stimuli, particularly fear-related information. Fear is central in the evolution of the mammalian brain: it is automatically and rapidly elicited by potentially dangerous and deadly events. The view that the amygdala shares the main characteristics of modular systems, e.g. domain specificity, automaticity, and cognitive impenetrability, has become popular in neuroscience. Because of its co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

82
586
3
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 819 publications
(696 citation statements)
references
References 0 publications
82
586
3
6
Order By: Relevance
“…In this context, the hypothesis that emotion processing is influenced by appraisal of selfrelevance assigned to a stimulus (i.e., self-relevance hypothesis) would predict different behavioral responses as a function of idiosyncratic representations of threat (Sander et al 2003). As reported above, subjects with high trait anxiety would be particularly prone to experience anxiety to cues subjectively signaling threats (fearful faces with averted gaze and angry faces with direct gaze),…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the hypothesis that emotion processing is influenced by appraisal of selfrelevance assigned to a stimulus (i.e., self-relevance hypothesis) would predict different behavioral responses as a function of idiosyncratic representations of threat (Sander et al 2003). As reported above, subjects with high trait anxiety would be particularly prone to experience anxiety to cues subjectively signaling threats (fearful faces with averted gaze and angry faces with direct gaze),…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation of the observed 5-HTTLPR effect might be that risk allele carriers are in general more sensitive in the automatic detection of biologically and socially relevant information in the environment. There is substantial evidence that the human amygdala is involved in the appraisal of events relevant for the survival and well-being of the organism (Ö hman, 2002;Sander et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated a key role for the amygdala in reinforcement learning during the processing of both positive and negative emotions (Sergerie et al, 2008;Sander et al, 2003, for a review), and in particular for learning the positive or negative value of external stimuli through their association with rewards and punishments (Paton et al, 2006). Peck and collaborators (2013) tested three rhesus monkey to determine how the amygdala could integrate spatial-visual and motivational information, and thus possibly influence the allocation of spatial attention.…”
Section: A Role For the Amygdala In Motivational Attention?mentioning
confidence: 99%